The Ezekiel generation the Father's heart for Israel and the Church in the last days - Berry, Grant (Shippensburg, PA: Destiny Image Publishers, Inc., 2013)
The Father's heart for Israel and the Church you live in one of the most critical hours in human history and G-d is calling you to participate! for the body of Christ to be most effective in these last days, unity is essential. We all have key roles to play in the unfolding of G-d's great agenda for history. Author Grant Berry is on a mission to help you find your place in this hour and see both Jew and Gentile unite to bring G-d's end time purposes to fruition.
Keywords: Bible. O.T. Ezekeil -- Textbook; Bible. O.T. Ezekiel; Religion -- Biblical studies -- Prophets